The Association Between Sleep Quality, Fatigue and Periodontal Status: a Pilot Study - Eroğlu, Zeynep Taştan (2023)
Reduced sleep duration, poor sleep quality and fatigue are related to reduced immunity and increased inflammatory markers. Due to its potential to influence inflammation, poor sleep quality and fatigue could be factors for periodontitis and quality of life. Ninety-three individuals with untreated periodontitis and thirty-one individuals with healthy gingiva were included in the study. The research involved a clinical examination and a questionnaire. Demographic information, information on oral health, oral hygiene habits, the Pittsburgh Sleep Quality Index, Jenkins Sleep Scale, Multidimensional Assessment of Fatigue Scale, and Oral Health Impact Profile-14 were included in the questionnaire. Patients were diagnosed based on the 2017 World Workshop on the Classification of Periodontal and Peri-Implant Diseases and Conditions. No statistically significant difference was revealed between sleep quality, fatigue, oral health related quality of life, and stage-grade of periodontitis (p<0.05). However, periodontitis group had higher Oral Health Impact Profile-14 scores (p<0.05). A statistically significantly lower sleep duration was observed in stage IV periodontitis group than the other groups (p<0.05). A statistically significant positive correlation was observed between the Pittsburgh Sleep Quality Index and the scores of the other questionnaires (p<0.05). The stage of periodontitis may impact sleep duration.